Islam Nusantara dalam Kerukunan Umat Beragama - Qurroh A’yuniyah; Akhmad Mahfud; Imamul Muttakin (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This research explores the role of Islam Nusantara in building religious harmony in Indonesia through a literature review approach. Islam Nusantara is known as a form of applying Islamic teachings that adapts to local culture, upholds moderation, and prioritizes the values of tolerance and social harmony. Through a literature review, this research identifies the core values of Islam Nusantara, its implementation strategies, and the challenges faced in a religiously and culturally diverse society. The results reveal that Islam Nusantara contributes significantly to maintaining social harmony through cultural approaches, promotion of interfaith dialogue, and moderation-focused education. However, challenges such as the rise of radicalism and the lack of religious literacy in society are obstacles that need to be overcome. Therefore, it is important to strengthen the understanding of Islam Nusantara through education and media approaches to support the sustainability of harmony amid diversity.